Faktor-Faktor yang Mempengaruhi Keputusan Investasi Syariah Mahasiswa di Kabupaten Bogor - Reza Maulana; Abrista Devi; Suyud Arief (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
The development of the economic and financial sectors has had a major impact on the increasing number of financial instruments and products offered as a form of adjustment to meet the needs & desires of the global community, one of which is sharia investment. Sharia investment instruments were developed to meet the needs of most of the world's Muslims in developing their assets with sharia principles. As one of the countries with the largest Muslim population in the world, Indonesia has enormous potential in sharia investment. But in fact, until now its market share is still relatively low.College students are a worthy target of market share to increase the rate of sharia investment in Indonesia because students have a high level of sensitivity to existing developments and are considered to have proper knowledge. In determining investment decisions, of course, there are factors that can influence investors, some of which include sharia investment, sharia financial literacy, religiosity, social environment, sociodemography, and investment returns.. In this study, the influence of these factors was identified on sharia investment decisions with students in Bogor Regency as subjects. Quantitative research is the method used by researchers with a sample of 100 respondents and the Structural Equation Modeling (SEM) method by IBM SPSS AMOS22 as the data analysis technique. The results showed that there was a significant & positive effect both simultaneously & partially on the variables of Islamic financial literacy, religiosity, social environment, sociodemography, and investment returns on Islamic investment decisions of students in Bogor Regency. Keywords: Sharia Investment, Islamic Financial Literacy, Religiosity, Social Environment, Sociodemography, and Investment Return.